2020
DOI: 10.1038/s41467-020-17395-y
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy deficiency promotes triple-negative breast cancer resistance to T cell-mediated cytotoxicity by blocking tenascin-C degradation

Abstract: Most triple-negative breast cancer (TNBC) patients fail to respond to T cell-mediated immunotherapies. Unfortunately, the molecular determinants are still poorly understood. Breast cancer is the disease genetically linked to a deficiency in autophagy. Here, we show that autophagy defects in TNBC cells inhibit T cell-mediated tumour killing in vitro and in vivo. Mechanistically, we identify Tenascin-C as a candidate for autophagy deficiency-mediated immunosuppression, in which Tenascin-C is Lys63-ubiquitinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 45 publications
2
86
2
Order By: Relevance
“…To date, various immunotherapeutic agents have been developed and improved in TNBC patients. Of which, immune checkpoint inhibitors represent particularly attractive, but anti-PD-1 or anti-PD-L1 antibody alone remains low response rate among TNBC patients [ 9 ]. This was partially attributed to immune suppression of anti-tumor T lymphocytes [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, various immunotherapeutic agents have been developed and improved in TNBC patients. Of which, immune checkpoint inhibitors represent particularly attractive, but anti-PD-1 or anti-PD-L1 antibody alone remains low response rate among TNBC patients [ 9 ]. This was partially attributed to immune suppression of anti-tumor T lymphocytes [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of which, immune checkpoint inhibitors represent particularly attractive, but anti-PD-1 or anti-PD-L1 antibody alone remains low response rate among TNBC patients [ 9 ]. This was partially attributed to immune suppression of anti-tumor T lymphocytes [ 9 ]. Additionally, previous reports indicated that elevated TILs levels are frequently associated with a lower risk of relapse and improved survival time in TNBC patients [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with that, autophagy-deficient 4T1 cells, through Atg5 or Beclin1 depletion with specific single guide(sg)RNA, generated larger tumors with reduced CD4 + and CD8 + TILs and IFNg + T cells in Balb/c mice, when compared to autophagy competent 4T1 cells. Moreover, the antitumor effect of the anti-PD1 antibody was limited in autophagy-deficient tumors, while a significant reduction in tumor volume and increased cytotoxic activity of TILs was observed in the control group (90). Similarly, a combination of anti-PD1 immunotherapy with anti-angiogenic endostatin, Endostar, promoted the activation of autophagy pathway PI3K/AKT/mTOR in LLC-bearing mice.…”
Section: Autophagy Improves New Therapeutic Strategies By Modulatingmentioning
confidence: 95%
“…Mammary tumor cells also produced transforming growth factor β1 (TGFβ1), which induced TNC expression in the surrounding stroma ( 25 , 26 ). Due to defective autophagy TNC seems to be highly abundant in triple negative breast cancer ( 27 ). An overview of factors regulating TNC expression is presented in Giblin et al ( 23 ).…”
Section: Introductionmentioning
confidence: 99%